Pemanfaatan Cangkang Telur Terenkapsulasi sebagai Adsorben: Karakterisasi dan Studi Kinetika Adsorpsi Metilen Biru - John Yoro Parlindungan; Rusnadi; Lamtiar Ferawaty Siregar; Jesi Jecsen Pongkendek (Jurnal Teknik Kimia USU, 2026)
The utilization of eggshell powder as an adsorbent presents certain limitations, particularly in terms of post-adsorption separation and the potential for clogging in column applications. To address these challenges, encapsulation was employed as a modification technique, wherein the eggshell powder was immobilized within a calcium alginate matrix to form a stable adsorbent structure. This study investigated the adsorption kinetics of methylene blue (MB) using three types of adsorbents: calcium alginate (CA), encapsulated eggshell powder (CA–SCKT), and unencapsulated eggshell powder (SCKT). Kinetic analysis was conducted using pseudo-first-order and pseudo-second-order models. The results indicated that the adsorption process for all adsorbents followed the pseudo-second-order kinetic model, as evidenced by higher correlation coefficient (R²) values.